Monotonic and Fatigue Performance of Double-skin Push-out and Tensile Segments of Divers Shear Connectors – Review - Alzahawy, Zainab Hussam; AL-Hadithy, Laith Khaled (Al-Nahrain Journal for Engineering Sciences, 2019)
Double skin composite (DSC) construction or Steel/concrete/steel sandwich construction (SCSS) is an innovative and relatively new form of composite construction that can be used in submerged tube tunnels, bridges deck, nuclear structures, liquid and gas containment structures, offshore and onshore structures, military shelters, and shear walls in buildings. The system consists of a plain concrete core sandwiched between two steel plates interconnected together by various types of mechanical shear connectors. The DSC construction perceives advantages that the external steel plates act as both formwork and primary reinforcement, and also as impermeable, blast and impact resistant membranes. The major duty of the shear connectors is to withstand longitudinal shear force and beam/slab separation, while in the bi-steel type where shear connectors are friction welded at both their two ends to two parallel steel plates, the longitudinal and transverse shear force, as well as plate buckling are resisted. The present paper highlights the previous prime researches concerning the subjects of SCSS composite construction, specifically on the conducted tests (push-out tests, tensile, direct shear tests, and bending tests) in which the components of partial interaction (uplift and slip forces) are resisted by various types of shear connectors.